Condições hídricas em sementes e mudas de jabuticabeira (Plinia sp.) - Radaelli, Juliana Cristina (2019)
This work was divided in two stages, one more specifically involving the use of seeds and the other of seedlings. In the first condition the germination behavior of the jabuticabeira seeds submitted to the hydrocondicionamento in different periods of time was evaluated, with influence of the storage temperature and the seed size. In the second, the behavior of seedlings submitted to water stress by means of different percentages of water in the substrate was observed, as well as, in flood condition of seedlings in water slides of five centimeters and stem height. Three experiments were carried out with seeds of jabuticabeira (Plinia sp.) Extracted from mature fruits, collected from a single plant of this institution. These seeds were hydrocondected for 0, 120, 240 and 360 hours at 5 ° C and 25 ° C (ambient) for the first experiment. In the second experiment, the seeds were separated in larger than 8 mm and smaller than 8 mm and hydrocondicionadas for periods of 0, 24, 48, 96 and 120 hours. The third experiment consisted of 24, 48, 72, 96, 120, 144, 168, 192, 216, 240, 264, 288, 312, 336, 360, 384, 408, 432, 456, 480 hours of water . After each period seeded Gerbox® box with lid, on moistened Germtest® paper, kept in controlled environment of 25 ºC. Seed germination (%), germination rate index (IVG) and mean germination time (TMG) were evaluated for 30 days after sowing of the three experiments. The second stage the experiments were carried out at UNEPE - Nursery Teaching and Research Unit of vegetable seedlings production and at the Laboratory of Plant Physiology, Federal University of Technology Paraná Câmpus Dois Vizinhos - Paraná. Jabuticaba saplings of four and 18 months were evaluated in relation to survival rate, leaf number, shoot height, stem diameter, and total dry matter mass (MST), total chlorophyll, quantum yield, protein content, total sugar and total phenols and proline in the field capacities of 100, 80, 60, 40, 20 and 0% and field capacity of 100, 75, 50, 25 and 0%, respectively. The seedlings were transplanted into 900 grams of commercially available substrate in transparent plastic bottles (PET®) with a capacity of two liters, without opening in the bottom for drainage of water and closed with aluminum foil to avoid evaporation of water from the substrate. In the third and fourth experiments, jabuticabeira seedlings of approximately 24 months and 18 months old were transplanted in plastic vats with a capacity of 3 liters, containing a substrate prepared in the proportion of 2: 1: 1 (v / v) of latosol, sand and poultry bed, respectively. After transplanting, the seedlings were submitted to flooding for periods of 0, 3, 5, 10 and 15 days and 0, 5, 10 and 15 days for the third and fourth experiments. Part of the plants will go through only one flood cycle and the remaining ones when 30 days have elapsed since they were removed by the same periods previously used. The variables evaluated for the third and fourth experiments were survival rate, leaf number, total plant height, stem diameter, root dry matter mass (MSR), shoot dry matter mass (MSPA) and mass of total dry matter (MST), Dickson quality index, total chlorophyll, quantum yield, protein, total sugar and total phenols and proline values. Seeds stored at 5 ° C had superior results for the percentage of germination and the mean time of germination when compared to those maintained during hydrocondicionamento at 25 ° C. When seeds larger than 8 mm were used, they were found to be viable for longer than the smaller ones. Seeds maintained in hydrocondicionamento for up to 456 hours maintained germination above 73%. The use of hydrocondicionamento in seeds of jabuticabeira helps in the process of maintenance of viability. Jabuticabeira seedlings submitted to different percentages of water in the substrate showed a lower survival rate when compared to seedlings submitted to flooding. The growth of jabuticabeira seedlings was not affected by the flood periods adopted. The quantum yield was equal to or below the threshold considered as damage of photosystem II, which is 0.80, demonstrating that under the conditions in which the seedlings were evaluated, the plants were not with the maximum production of photosynthesis. The biochemical variables, proteins, total sugars, total phenols and proline were not influenced by the percentage of water in the substrate, as well as for seedlings submitted to flooding with a water slide of five centimeters. In seedlings submitted to flood periods at the height of the cervix and with substrate water levels of 0, 25, 50, 75 and 100%, there was a change in proline content.